Political theory and political science, the case for methodological naturalization - Aberdein Abbotte; Amy Smith (Al-Qanṭara, 2022)
Modern political theory demonstrates a shift toward data-driven research. Waldron, Shapiro, Carens, Blau, and Floyd emphasize the importance of empirically grounding political theory. Political scientists devised methods to improve the way political institutions are studied. What can empirical political theory learn from this literature to help it achieve its goal of precisely evaluating political institutions? It is proposed to naturalize political-science methods within political theory. We highlight three approaches: using case studies, avoiding sampling by dependent variable, and process tracing. To demonstrate their relevance, we re-read three studies in contemporary political theory (by Walzer, Spinner-Halev, and Wenar) using the methods described above. If empirical political theory seeks to achieve its stated objectives.